An Exploratory Investigation of the Role of Parenting Stress in Relationship Focused Intervention. Issue 6 (1st March 2015) - Alquraini, Turki; Mahoney, Gerald
<x xml:space="preserve">Abstract</x> Background Mothers of young children with Pervasive Developmental Disorders (PDD) and other disabilities (DD) have been reported to experience high levels of stress. This investigation examined the effects of parental stress on mothers? participation in a Relationship Focused intervention (RFI). Methods Mothers and young children who had either PDD (n = 18) or DD (n = 26) received weekly RF intervention for one year. Results Pre‐post comparisons indicated significant increases in mothers? responsiveness and children?s development and social emotional functioning. Intervention effects were greater for mothers of children with PDD than for mothers of children with DD. There were three findings related to the role parenting stress. First, high levels of parenting stress did not interfere with mothers? ability to learn RFI strategies; second, there were non‐significant decreases in parenting stress during intervention; third, parenting stress enhanced the effects of mothers? responsiveness on children. Conclusion High levels of parenting stress does not appear to interfere with parent participation in RFI.